Redox Imbalance Differentially Inhibits Lipopolysaccharide-Induced Macrophage Activation in the Mouse Liver - Wang, Fuan (American Society for Microbiology, 1999)
Endotoxemia is accompanied by significant changes in the reductive-oxidative (redox) balance of critical target organs. Redox stress has been shown to regulate the expression of proinflammatory genes that are induced by endotoxic lipopolysaccharide (LPS) in vitro; however, much less is known about the effects of redox imbalance on LPS-induced gene expression in vivo. To assess the effects of redox stress on inflammatory responses in endotoxemia, mice were treated with either diethyl maleate (DEM), a glutathione-depleting agent, or buthionine sulfoximine (BSO), an inhibitor of glutathione synthesis, and challenged with LPS. While serum tumor necrosis alpha (TNF-α) responses and the appearance of TNF-α-positive Kupffer cells in the liver were virtually eliminated by DEM or BSO treatment, the expression of both CD14 and inducible NO synthase (iNOS) by Kupffer cells was unaffected by glutathione depletion. By contrast, LPS-induced hepatocyte and hepatic sinusoidal endothelial cell iNOS expression was significantly inhibited in DEM-treated mice. Hepatocyte iNOS induced by recombinant mouse TNF-α was also inhibited by DEM treatment. These results indicate that the effects of oxidative stress in this organ are cell type specific and suggest that both the production and the action of TNF-α are substantially influenced by the redox state of the liver during endotoxemia.